Putting nutrition education on the table: development of a curriculum to meet future doctors' needs. Issue 6 (28th March 2023) - Jones, Glenys; Macaninch, Elaine; Mellor, Duane D.; Spiro, Ayela; Martyn, Kathy; Butler, Thomas; Johnson, Alice; Moore, J. Bernadette
Abstract: COVID-19 has further exacerbated trends of widening health inequalities in the UK. Shockingly, the number of years of life lived in general good health differs by over 18 years between the most and least deprived areas of England. Poor diets and obesity are established major risk factors for chronic cardiometabolic diseases and cancer, as well as severe COVID-19. For doctors to provide the best care to their patients, there is an urgent need to improve nutrition education in undergraduate medical school training. With this imperative, the Association for Nutrition established an Interprofessional Working Group on Medical Education (AfN IPG) to develop a new, modern undergraduate nutrition curriculum for medical doctors. The AfN IPG brought together expertise from nutrition, dietetic and medical professionals, representing the National Health Service (NHS), royal colleges, medical schools and universities, government public health departments, learned societies, medical students, and nutrition educators. The curriculum was developed with the key objective of being implementable through integration with the current undergraduate training of medical doctors. Through an iterative and transparent consultative process, thirteen key nutritional competencies, to be achieved through mastery of eleven graduation fundamentals, were established. The curriculum to facilitate the achievement of these key competencies is divided into eight topic areas, each underpinned by a learning objective statement and teaching points detailing the knowledge and skills development required. The teaching points can be achieved through clinical teaching and a combination of facilitated learning activities and practical skill acquisition. Therefore, the nutrition curriculum enables mastery of these nutritional competencies in a way that will complement and strengthen medical students' achievement of the General Medical Council (GMC) Outcome for Graduates. As nutrition is an integrative science, the AfN IPG recommends that the curriculum is incorporated into initial undergraduate medical studies before specialist training. This will enable our future doctors to recognise how nutrition is related to multiple aspects of their training, from physiological systems to patient-centred care, and acquire a broad, inclusive understanding of health and disease. In addition, it will facilitate medical schools to embed nutrition learning opportunities within the core medical training, without the need to add in a large number of new components to an already crowded programme or with additional burden for teaching staff. The undergraduate nutrition curriculum for medical doctors is designed to support medical schools to create future doctors who will understand and recognise the role of nutrition in health. Moreover, it will equip frontline staff to feel empowered to raise nutrition-related issues with their patients as a fundamental part of enhanced care and to appropriately refer on for nutrition support with a registered associate nutritionist/registered nutritionist (ANutr/RNutr) or registered dietitian (RD) where this is likely to be beneficial.